Dari Pionir ke Korporasi: Evolusi Deli Maatschappij dan Perekonomian Lokal di Sumatera Timur (1864–1924) - Hafiz Fadhlan; Fajriudin; Amelia Sri Andini (Historia Madania: Jurnal Ilmu Sejarah, 2025)
The trend of cigar smoking in Europe around the 19th century had a significant impact on the Deli Sultanate in East Sumatra. This trend necessitated a substantial supply of tobacco in Europe to ensure continued enjoyment. One of the countries that played a crucial role in tobacco cultivation was the Dutch East Indies government. The Dutch chose to cultivate tobacco in East Sumatra because it was considered to have the natural resources and soil suitable for this cultivation. This study aims to determine the existence of the Deli Sultanate and the history of plantations in East Sumatra before 1864. It also aims to examine the development of tobacco plantations during the Deli Sultanate in East Sumatra between 1864 and 1924, as examined in terms of supply and demand from the European market. This study employed a historical research method consisting of four stages: heuristics, or the collection of primary and secondary sources; criticism, or the selection of sources, consisting of internal and external criticism; interpretation, or the interpretation of sources; and finally, historiography, the process of writing history. Based on the research that has been done, the Deli Malay Sultanate originated from the Aru Kingdom in the 13th century AD, which has played an important role in the history of the development of Medan City, especially since the opening of tobacco plantations in 1863. The reign of Sultan Mahmud Al-Rasyid marked the beginning of the progress of civilization in East Sumatra, with his approval of cooperation with the Dutch, namely Jacobus Nienhuys in the opening of tobacco plantations. High-quality Deli tea brought a significant economic impact, including a surge in demand from the European market in 1865. This development also influenced the social and economic structure of the Deli Sultanate as well as the European market. Modern infrastructure such as the railway and the Belawan port were built as a result of the expansion of tobacco plantations, while foreign companies also invested in the Deli region. The period 1864-1924 was marked by the leadership of Sultan Mahmud Al-Rasyid Perkasa Alamsyah and Sultan Makmun Al-Rasyid Perkasa Alamsyah where significant progress occurred in various existing fields.